2017
DOI: 10.1039/c7cp05334g
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfide intercalation in bilayer-structured graphitic C3N4: a first-principles study

Abstract: Lithium-sulfur (Li-S) batteries have attracted increasing attention due to their high theoretical capacity, being a promising candidate for portable electronics, electric vehicles and large-scale energy storage. The interactions of bilayer structured graphitic CN (bi-CN) with S, lithium polysulfides (LiPSs), 1,3-dioxolane, 1,2-dimethoxyethane and tetrahydrofuran ether-based solvents have been studied using first-principles calculations. It has been found that the (micropore-scale) interlayer of bi-CN shows int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…[ 66,67,70,71 ] To further understand how the SG nanosheets adsorb different polysulfides at the molecular level, the optimized adsorption configuration was simulated for both Li 2 S and Li 2 S n based on the Castep model. [ 72,73 ] The bonding energies (Δ E b ) of Li 2 S n species with SG were calculated using Equation (1). ΔEnormalbLi2Sn=ELi2Sn/SGELi2SnESG …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 66,67,70,71 ] To further understand how the SG nanosheets adsorb different polysulfides at the molecular level, the optimized adsorption configuration was simulated for both Li 2 S and Li 2 S n based on the Castep model. [ 72,73 ] The bonding energies (Δ E b ) of Li 2 S n species with SG were calculated using Equation (1). ΔEnormalbLi2Sn=ELi2Sn/SGELi2SnESG …”
Section: Resultsmentioning
confidence: 99%
“…This result indicates a very strong chemical interaction between the SG surface and the PSs. [ 71–73 ]…”
Section: Resultsmentioning
confidence: 99%
“…Graphitic C 3 N 4 is a polar non-metal material [15], which includes three types of nitrogen in its intrinsic structure: pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen [16]. It has been theoretically and experimentally testified [17,18] that the primary active sites are pyridinic nitrogen, which can interact with LiPSs to accelerate the electrochemical conversion processes and lessen polarization. Pyridinic nitrogen is sp 2 hybridized with lone pair electrons, so it can generate chemical interaction with LiPSs via Li−N to suppress shuttle-effect and improve the performance of Li-S batteries [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of layer structured graphitic C 3 N 4 with S 8 and LiPSs have also been studied using firstprinciples calculations. The results showed that graphitic C 3 N 4 had a physical and strong binding with S 8 (which may result in improved sulfur loading) and it also had a chemical and stronger interaction with LiPSs [18]. Layered graphitic C 3 N 4 as host material has been proved with many advantages.…”
Section: Introductionmentioning
confidence: 99%
“…With this cell, an initial areal capacity of 4 mAh cm -2 was obtained with a retention areal capacity of 2.7 mAh cm -2 after 300 cycles at 0.1 C More recently, Fan et al [91] used a macromolecule graphitic carbon nitride (g-C3N4)coating as an effective PS barrier with a high sulfur loading (S loading: 5 mg cm -2 ) (Figure 2.9c). The pyridinic-N groups of g-C3N4 provide strong polar-polar interaction sites for the PS -improving the long-term cell stability[92]. The g-C3N4 coated separator cell delivered an initial discharge capacity of 5.98 mAh cm -2 (S loading: 5 mg cm -2 ) at 1 C with a retention capacity of 4.11 mAh cm -2 after 400 cycles.…”
mentioning
confidence: 99%